A systematic review of the effect of daily panty liner use on the vulvovaginal environment. Issue 1 (30th July 2014) - Pontes, Ana C.; Amaral, Rose L.G.; Giraldo, Paulo C.; Beghini, Joziani; Giraldo, Helena P.D.; Cordeiro, Etienne S.
Abstract: Background: Whether panty liners predispose to vulvovaginitis is unclear. Objectives: To clarify the effects of the use of panty liners on the female genital tract. Search strategy: Several electronic databases (including PubMed and Embase) were searched to identify studies published in English before May 3, 2012. Selection criteria: Case–control studies, randomized controlled trials, and cohort studies comparing young women who did and did not use panty liners in the intermenstrual period were included. Data collection and analysis: The quality of the studies was assessed using the Newcastle–Ottawa Scale or the Jadad Scale. Data from suitable studies were extracted for analysis. Main results: Five articles met the inclusion criteria. Four studies—all of which included only healthy women—found no significant clinical implications arising from the use of panty liners. The fifth study was of women with recurrent candidiasis and showed that use of panty liners was associated with new candidiasis episodes. Conclusions: The intermenstrual use of panty liners does not seem to have a negative effect on the vulvovaginal area.